A Systems Study on the National Manpower and Youth Council Development Institute - Agutaya, Yvonne Felisse F.; Cantoria, Domingo Jose M.; Derecho, Arthur D.; Frianeza, Wilfredo S.; Gutierrez, Marley B.; Manaloto, Diosdado M.; Ramel, Erwin Arsenio G., III; Santos, Jorge G.; Sison, Ruben R.; Ulep, Corabelle R. (College of Engineering, 1984)
The objectives of the following study are: to conduct a total system study of the National Manpower and Youth Council Development Institute (NDI), its objectives, functions, subsystems and external environment, and to recommend improvements on the existing system; in conjunction with the total system study, to conduct a study of the management information system of the NDI, and to recommend improvements on the existing system; and to highlight factors to be considered in the implementation of the recommended improvements, and to point out areas that need further study. The methodology of the group that made the study is as follows. First, the group employed the use of interviews, concept papers, and manuals of the NMYC and the NDI to document the system under study. This consisted of documenting the personnel, systems and procedures, information system, and tools, equipment, and facilities of the system; and describing the environment in which the system under study is expected to operate. Second, the group analyzed the system under study. This consisted of defining criteria for the design of a system to achieve the NDI's objectives; and evaluating the system under study according to the defined criteria. Third, the group generated an alternative design for the system under study according to the defined criteria. Fourth, the group generated an implementation process for the alternative design. This consisted of anticipating the resisting forces that might be encountered in the implementation; and recommending methods in implementation that will overcome the resisting forces and attain stability. A predecessor of the NDI is the Manpower Development Council (MDC) which was created on Dec. 8, 1966 when manpower development was integrated with various government programs. The MDC carried out manpower training programs until Feb. 27, 1969 when the Manpower and Out-of-school Youth Development Act was enacted under the then Department of Labor. The act was signed into a law on March 19, 1969 and the NMYC was created. On September 5, 1978, the Council was transferred from the Ministry of Labor to the Office of the President. The objectives of the NMYC are: to promote employability and productivity of workers through the conduct and coordination of skill training programs; to assist in employment creation; and to enhance the character of the Filipino workers. The NDI was created on November 11, 1983 to replace the Human Resource Development Unit (HRDU). Its only objective then was to strengthen the staff development program of NMYC. In January of 1984, the NDI was also made responsible for the coordination of the corporate planning process of NMYC, a responsibility that made the approach to staff development a more holistic one. The position of the NDI within NMYC is a staff function to the Office of the Director General. The objectives of the NDI are: to cause the developments of the organization of NMYC units and their management; and to effectively and efficiently implement the staff development program of the Council. It is headed by the Board of Trustees which is composed of the Director General as Chairman, the Deputy Director General as Vice Chairman, and all members of the Directorate as members. Directly below the Board of Trustees is the managing staff composed of the Managing Director assisted by the Deputy Managing Director. Four development departments report directly to the Deputy Managing Director. The Executive Development, Professional/Technical Development, and Employee Development Departments serve as advisers to the staff development arm of the NDI, the Training and Development Group (TDG). The fourth, which is the Organization and Management Development Department, serve as adviser to the Corporate Planning Group (CPG). Both the TDG and CPG report to the NDI Management Staff Chief who in turn reports to the managing group like the four Development Departments. A third group that reports to the NDI Management Staff Chief is the Administrative Services Group which assists the other two groups in their paper work as well as in their primary functions. The TDG has developed procedures for some of its functions. Documented are their procedures for designing training programs and selecting trainees for study grants outside the NMYC. On the other hand, the CPG has procedures for instituting NMYC's corporate planning process. The present information systems of both the TDG and the CPG were documented and studied. It could be said that information flows between the NDI units are often undefined owing to the nonexistence of procedures for the staff development functions. The organization structure of the NDI should be compatible with the structure of the NMYC as a whole; reflect that the major objectives and functions of the NDI are given due to importance in organizing the structure; reflect that only those needing to operate separately are presented as separate components; and reflect ease of operations of both the whole structure and its components. The procedures of the NDI should be presented as a series of steps and each step should be clearly stated. Procedures which can be done simultaneously should be indicated as so; and that they should only go as far as their functions indicate. With respect to the names of the subgroups of the NDI, Training and Development Group hardly indicates that it is primarily concerned with the organization and management development. Procedures for the activities of the NDI lack detail on how to go about performing specific tasks covered by their functions. Also, the NDI lacks a well-defined information system. This is due to the fact that the detailed systems and procedures have not yet been established. The foregoing analysis was based on a concept paper written by the NDI Management Staff. The said paper is not however an official document of the NDI. It is recommended that the name of the Training and Development Group, and the name of the Corporate Planning Group be changed to Organization and Management Development Group. It is also recommended that the Administrative Services Group be abolished and personnel be assigned to the tasks on a separate basis. The four development departments are recommended scrapped since they only act as advisers. It is recommended that the Advisory Committees composed of consultants and coaches replace them. The functions of the NDI can be divided between the resulting two groups namely PTDG and OMDG. These two sets of functions have recommended procedures for their implementation. From these procedures, information systems are presented. Implementations of the recommendations have to take into consideration the present system especially its present personnel. A recommendation can only be as good as the way it was implemented. Areas for further study presented here generally result from the limitations for the group making the study.